Невидимый папа: [повесть] / Дарья Доцук - Доцук Дарья Сергеевна (Современная проза, 2015)
Экземпляры: ф.18 (20200616) / Инвентарный номер: 3412 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 71 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44